AI as Aid Tool in Visual Programming Courses at Universitas Multimedia Nusantara - Purnama, Hadi; Hefira, Vania (ULTIMART Jurnal Komunikasi Visual, 2025)
This research investigates AI usage within a Visual Programming course at Universitas Multimedia Nusantara, focusing on how design students integrates AI into interactive media development. In this case, the output is game development using Unity platform that requires fundamental programming logic. This study aimed to assess AI's involvement in the development process and explore its limitations for programming for design students. Data was collected via questionnaires (n=44) and continued by interviews (n=8) to further pursue insights on AI's potential to replace programmers. The questionnaire results showed 100% of the respondents use AI across various game development stages, from ideation and story development to asset creation, soundtracks, programming, and animation. The practical application of AI in a first-person controller game demonstrated its effectiveness for generating basic code, but also highlighted the need for human intervention in debugging, adaptation, and quality assurance. The interview reveal students’ challenges with faulty logic AI solutions. The research concludes that AI is a valuable programming assistant during game development, expanding human capabilities, but cannot fully replace human understanding of programming logic, problem-solving, and creativity. This underscores the importance of strategically integrating AI into curricula to enhance, but not replace, human learning and programming skills. Keywords: visual communication design; technology of artificial intelligence; learning assistance